Beyond Google2019;s PageRank: Complex Number-based Calculations for Node Ranking (Global Journal of Computer Science and Technology, 2019)
This study is focused on a proposed alternative algorithm for Google's PageRank, named Hermitian centrality score, which employs complex numbers for scoring a node of the network to overcome the issues of PageRank2019;s link analysis. This study presents the Hermitian centrality score as a solution for the problems of PageRank, which are associated with the damping factor of Google2019;s algorithm. The algorithm for Hermitian centrality score is designed to be free from a damping factor, and it reproduces PageRank results well. Moreover, the proposed algorithm can mathematically and systematically change the point of a node of a network.
Keywords: search engine; PageRank; damping factor; complex number; hermitian adjacency matrix